A narrative review on the role of cytokines in the pathogenesis and treatment of familial Mediterranean fever: an emphasis on pediatric cases - Chaaban, Ahlam; Yassine, Hasan; Hammoud, Razane; Kanaan, Ruba; Karam, Louna; Ibrahim, José-Noel (Frontiers in Pediatrics, 2024)
Familial Mediterranean Fever (FMF) is a hereditary autoinflammatory disease characterized by an early onset of recurrent fever and serositis episodes. FMF is caused by mutations in the MEFV gene which encodes the pyrin protein, an IL-1β mediated inflammation regulator. Recent findings have identified a plethora of molecules and pathways involved in the regulation of inflammation and innate immunity, hence increasing our understanding of the etiology and inflammatory nature of FMF. Cytokines, in particular, have been found to play a key role in the pathogenesis and treatment of the disease. Indeed, various studies associated cytokines' genetic variations and expression with susceptibility to and severity of the disease, which was further supported by the positive response of patients, both children and adults, to targeted cytokine blocking therapies. These studies highlighted the potential use of cytokines as biomarkers and target in resistant/intolerant patients and contributed to improving the early detection of FMF in children, thus enhancing their quality of life and providing alternative treatment for severe cases. The aim of this review is to provide the latest updates on the pivotal role of cytokines in FMF and to discuss the efficacy and safety of anti-cytokine biologics by primarily focusing on pediatric FMF cases.• Familial Mediterranean Fever• Exploring cytokine profile and signature in FMF provides new insights into the pathways and mechanisms involved in the disease pathogenesis. • Cytokine studies in pediatric FMF are challenging yet crucial to design early and accurate diagnostic and therapeutic strategies that could improve patients' quality of life.• Anti-cytokine therapy, mainly IL-1 inhibitor, represents a safe and efficient approach to treat FMF children that are resistant/intolerant to colchicine. • Future studies and clinical trials investigating the effect of anti-cytokine therapy in FMF should include a more representative heterogenous sample with longer follow-up durations and a wider scope of biologics (anti-IL-17, anti-IL-18, etc.). • Designing combinational therapeutics could offer new solutions for refractory FMF patients, especially those with cytokine genetic variations associated with FMF onset and severity.